Legal Certainty of Drivers' Status for Travel Entrepreneurs from the Perspective of Law Number 13 Of 2003 Concerning Employment - Sugeng Prayitno; Nyi Ayu Habibah Marwa Decika (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Legal certainty in employment relationships is a foundation used by workers (drivers) and employers aimed at preventing arbitrary actions as well as legal violations. Legal certainty is expressed in the form of agreements as a basis for recognition of the status of workers (drivers); however, in reality, the employment relationship between drivers and travel companies is only based on partnership agreements. In fact, these agreements are used by companies to avoid obligations towards workers under labor law. This practice often causes imbalances, because even though an employment relationship exists with elements of work, orders, and wages, workers do not obtain the normative rights as regulated in labor law. Based on the principle of freedom of contract in Article 1338 of the Civil Code, partnership agreements are valid as long as they do not conflict with laws, morality, and public order. However, when the substance of the legal relationship indicates the fulfillment of the elements of an employment relationship, then that relationship should be subject to labor law provisions. The research method used is normative juridical with a statutory approach and a case study of two decisions of the Industrial Relations Court (PHI) involving PT Niaga Handal Cemerlang or Arnes Shuttle. In both decisions, the panel of judges stated that the relationship between the driver and the company met the elements of an employment relationship, and therefore must comply with labor law provisions. The research results show a legal vacuum in the labor legislation system in Indonesia, especially in providing a clear boundary between partnership relations and employment relations. This vacuum has created room for the practice of disguised employment, which is the concealment of standard employment relationships as non-standard relationships to avoid legal obligations to workers. This will impact legal uncertainty for drivers, who ultimately do not receive legal protection, because certainty and legal protection are obtained when the substance of the agreement regulates such matters. Therefore, it is necessary to establish legal norms that explicitly provide clear and firm boundaries between partnership relations and employment relations. In addition, Indonesia also needs to promptly ratify ILO Recommendation No. 198 of 2006 on Determining Employment Relationships in order to strengthen the national legal framework in protecting workers, as well as to provide legal certainty for workers employed as drivers.